Correlation between Critical Thinking Skills and Students' Learning Interests in the Development of Website-Based Learning Media Using the SQ3R Method - Destian, Rangga; Wahyudin, Wahyudin; Megasari, Rani (Journal of English Language and Education, 2025)
The problem of low scores in Informatics subjects, student literacy, and critical thinking skills are the main background of this research. To answer these challenges, this study aims to develop website-based learning media using the SQ3R (Survey, Question, Read, Recite, Review) method in learning programming algorithms, and to measure the influence and correlation between students' learning interests and critical thinking skills. The subjects in this study were grade X students of the Software and Game Development Expertise Program (PPLG) at SMKN 1 Cisarua, with the object of research being students' critical thinking skills and learning interests. The research method used is Research and Development (RD) with the ADDIE development model, which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Learning media are designed to provide an interactive and enjoyable learning experience that supports the development of critical thinking skills and increases students' interest in learning programming algorithm material. The research instruments consisted of a learning interest questionnaire, a critical thinking test, and a validation sheet from material and media experts. The validation results showed that the developed media was feasible to use. Data analysis showed that there was a low positive correlation between students' learning interests and critical thinking skills, with a correlation coefficient value of 0.27. The conclusion of this study is that there is a relationship between students' learning interest and critical thinking skills, although the relationship is included in the low category. The developed learning media has the potential as an effective tool in improving the quality of the programming algorithm learning process.